Penerapan Manajemen Lalu Lintas Sirkulasi Arus Satu Arah pada Simpang Jalan Teuku Umar Barat - Jalan Gunung Salak Kota Denpasar - Theodorus, Alfonsus (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Teuku Umar Barat – Gunung Salak Street Intersection is one of the intersections that serves high traffic movement in the West Denpasar area. The problems that occur at the intersection are traffic congestion with high delays, especially during rush hours. To improve the performance of the intersection so that efficiency and smooth traffic flow can be achieved, a study was conducted with the aim of regulating traffic management in the intersection area with a one-way flow circulation pattern. Analysis of the performance of the section and intersection in existing conditions and the planned scenario using MKJI 1997, there are two alternative traffic managements, namely Alternative 1: Diverting Traffic Movement on the North and South Legs (North Gunung Salak Street – South Gunung Salak Street) multi-program traffic signal arrangements. Alternative 2: Diverting Traffic Movement on the East and South Legs (West Teuku Umar Street – South Gunung Salak Street) with traffic signal arrangements. The results of the analysis show that Alternative 2 is the best solution to reduce the amount of delays and increase the capacity and level of service at the Teuku Umar Barat – Jalan Gunung Salak intersection.